The Effects of Milk and Posterior Intestinal Microorganisms on the Lactation Performance of Dual-Purpose Cattle (Bos taurus) Revealed by 16S rRNA Sequencing - Weitao Wang; Shengchao Ma; Dan Wang; Lei Xu; Menghua Zhang; Mengjie Yan; Kailun Ma; Zexu Hu; Yanyan Shang; Jiangjiang Wei; Xixia Huang (Microorganisms)
The aim of this research was to employ 16S rRNA high-throughput sequencing to thoroughly explore the interplay between milk and hindgut microbial communities and the effects of microorganisms in milk and the hindgut on the dairy quality of XJBC and CSC. In this study, 96 XJBC milk samples, 94 XJBC hindgut samples, 100 CSC milk samples, and 93 CSC hindgut samples were collected for microbial community analysis. The 16S rRNA sequencing data revealed that the microbial species richness in the milk of CSC exceeded that of XJBC, whereas the opposite was true for the hindgut microbial communities. A chi-square test was conducted using SPSS 19.0. The milk and posterior intestinal microbiota between individuals were analyzed with the Pearson chi-square test, maximum likelihood ratio, and Fisher’s exact test. Nongenetic factors substantially influenced microbial community dynamics in both milk and the hindgut. In the milk of dairy cows, a significant negative correlation was observed between one genus and milk protein production. Nine genera were significantly negatively correlated with milk fat production, whereas one genus was positively correlated. Additionally, six genera were negatively correlated with lactose production, and two genera exhibited positive correlations. Notably, Phascolarctobacterium and Turicibacter were identified as genera originating from the hindgut, which led to reduced milk quality. In the hindgut microbial community of dairy cows, seven genera were significantly negatively associated with milk fat production, whereas one genus was positively associated with milk fat production. These findings indicate that certain mammary microorganisms may migrate from the hindgut, either endogenously or exogenously, disrupting the equilibrium of the mammary microbial community in dairy cows and potentially leading to inflammation. By enhancing feeding conditions and standardizing production practices, the invasion of harmful flora into mammary tissues can be minimized, reducing the risk of inflammation and thereby preserving the health of dairy cows and enhancing milk quality.